Cochlear implantation outcomes in children with multiple disabilities: a topic that’s worth revisiting - Goh Bee-See; Nur Af’Idah Mohd Zulkefli; Asma Abdullah; Cila Umat; Norazlin Kamal Nor; Juriza Ismail; Stephen J. O’Leary (Brazilian Journal of Otorhinolaryngology, 2024)
Objectives: To determine the benefits of cochlear implantation in hearing loss children with multiple disabilities (MD) in terms of auditory outcomes, speech performance, and their quality of life. Methods: This was a cross sectional study from January 2019 to December 2020 in which thirty-one children with hearing loss and multiple disabilities were evaluated. Their improvement in auditory and speech performances were assessed using Categories of Auditory Performance version II (CAP-II) and the Speech Intelligibility Rating (SIR) scales. The assessment was done at 6-month intervals, with the baseline evaluation done at least six months after activation of the implant. Parents were asked to fill the Parents Evaluation of Aural/Oral Performance of Children (PEACH) diary and Perceived Benefit Questionnaire (PBQ) to evaluate the child’s quality of life. Results: All 31 children have Global Developmental Delay (GDD), with 11 having an additional disability. Both mean CAP-II and SIR scores showed significant improvement with increased hearing age (p < 0.05) after 6-month intervals. In addition, 20 out of 31 children (64.5%) have achieved verbal communication after implantation. The mean PEACH score in quiet was significantly better than in noise (p = 0.007) and improved with the increased of hearing age. The majority of parents (96%‒100%) perceived a cochlear implant as beneficial to their child in terms of auditory response, awareness, interaction, communication, and speech development. Conclusions: Cochlear implantation had shown benefits in children with multiple disabilities. Outcome measures should not only focus on auditory and speech performances but the improvement in quality of life. Hence, individualized each case with realistic expectation from families must be emphasized in this group of children. Level of evidence: Level 3.